Pengaruh Risiko Kredit terhadap Profitabilitas pada Bank Perkreditan Rakyat di Kepulauan Riau - Alexander, Alexander; Cuandra, Fendy (Jurnal Ilmiah Poli Bisnis, 2023)
The purpose of this research was to determine the effect of credit risk, liquidity risk, leverage, bank size, operating efficiency, inflation, gross domestic sales on profitability. This research uses quantitative method techniques and uses a purpose sampling method in analyzing research objects which also uses cross section and time series studies. The object of this research is the Rural Banks in the Riau Islands. A sample of 35 Rural Banks registered with the Financial Services Authority in the period 2017 to 2022. Data analysis used the SPSS Statistics 25 application and EViews 12 to obtain descriptive statistical data, panel regression analysis, F test, t test, and coefficient of determination. The results show that there is a significant influence on several variables. Where the variables credit risk, leverage, bank size, operating efficiency and inflation have a significant negative effect on profitability and the gross domestic gross variable also has a positive relationship with profitability. Meanwhile, liquidity risk has no influence on the profitability of Rural Banks in the Riau Islands.